2018
DOI: 10.1177/0963689718817760
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Near-Infrared Spectroscopy Monitoring in Carotid Endarterectomy: A Prospective, Single-Center, Observational Study

Abstract: There has been no gold standard for intraoperative monitoring in carotid endarterectomy (CEA) till now. The purpose of the current study was to investigate the value of near-infrared spectroscopy (NIRS) monitoring in CEA and explore the thresholds for intraoperative cerebral hypoperfusion. Eighty-four consecutive patients who underwent CEA surgery in Xuan Wu Hospital of Capital Medical University from August 2015 to June 2016 were enrolled in this study. All patients were intraoperatively monitored by transcra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…Twenty percent or more reduction in rSO 2 during ICA clamping is associated with a 10-fold increase in ischemic stroke [14]. The values measured with NIRS are consistent with transcranial doppler and a 12.3% reduction from baseline in rSO 2 can be used as a reliable threshold for intraoperative cerebral perfusion [15]. Moreover, it aids in avoiding carotid artery manipulation by reducing unnecessary use of shunts which may result in dissection or embolism [16].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Twenty percent or more reduction in rSO 2 during ICA clamping is associated with a 10-fold increase in ischemic stroke [14]. The values measured with NIRS are consistent with transcranial doppler and a 12.3% reduction from baseline in rSO 2 can be used as a reliable threshold for intraoperative cerebral perfusion [15]. Moreover, it aids in avoiding carotid artery manipulation by reducing unnecessary use of shunts which may result in dissection or embolism [16].…”
Section: Discussionmentioning
confidence: 58%
“…The mean age of the patients was 70.96 ±8. 15 ORIGINAL PAPER patients had a neurological sequela due to stroke preoperatively. Coronary artery disease was detected in 56 (73.6%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Yu Wang et al (12) found that the sensitivity and specificity of NIRS monitoring for intraoperative hypoperfusion were 64.3% and 90.0%, resulting in a strong consistency with TCD monitoring results. JM Findlay et al ( 13) compared stump pressures and NIRS measurements in CEA operations in terms of shunt placement and reported that NIRS was more accurate than stump pressure measurement.…”
Section: Discussionmentioning
confidence: 88%
“…Pedrini et al also used a 20 % decrease as a cut-off value for the shunt insertion; they reported no postoperative stroke or death. Wang with coworkers in 2019, compared TCD and TCO in 84 patients undergoing carotid endarterectomy in general anesthesia, the false-positive results and positive were worse, but they used 12.5 % decrease as a cut-off value for inserting (21). However, the authors reported no postoperative stroke or death in their cohort.…”
Section: Discussionmentioning
confidence: 99%